Huntington’s Disease Clinical Trials Corner: August 2018 - Rodrigues, Filipe B. (J Huntingtons Dis, 2018)
In the third edition of the Huntington’s Disease Clinical Trials Corner we list all currently registered and ongoing clinical trials, expand on the SIGNAL trial (NCT02481674), and cover the recently finished CREST-E trial (NCT00712426).